Excessive consumption of mucin by over-colonized Akkermansia muciniphila promotes intestinal barrier damage during malignant intestinal environment - Qu, Shuang; Zheng, Yinghui; Huang, Yichun; Feng, Yicheng; Xu, Kunyao; Zhang, Wei; Wang, Yawen; Nie, Kaili; Qin, Meng (Frontiers in Microbiology, 2023)
Gut microbiota disorders damage the intestinal barrier, which causes intestinal disease. Thus, we screened the microbiota with significant changes using an in situ malignant colorectal cancer (CRC) model. Among the colonies with increased abundance, Akkermansia muciniphila (A. muciniphila) is known for its characteristic of breaking down mucin, which is an essential component of the intestinal barrier. The role of A. muciniphila remains controversial. To investigate the effect of excess A. muciniphila on the intestinal barrier, we established an over-colonized A. muciniphila mouse model by administering a live bacterial suspension after disrupting the original gut microbiome with antibiotics. The results showed that over-colonization of A. muciniphila decreased intestinal mucin content. The mRNA and protein expression levels of tight junction proteins also decreased significantly in the over-colonized A. muciniphila mouse model. Our findings reveal that excess colonization by A. muciniphila breaks the dynamic balance between mucin secretion and degradation, reduces the thickness of the intestinal mucus layer, and damages the intestinal barrier, which would eventually aggravate the development of colitis and CRC. These results will raise awareness about the safety of A. muciniphila serving as a probiotic.